Brief Report: Sex Differences in the Association Between Cerebrovascular Function and Cognitive Health in People Living With HIV in Urban China. (1st March 2023) - Chow, Felicia C.; Zhao, Fang; He, Yun; Song, Xiaojing; Zhang, Jiangxia; Ao, Donghui; Wu, Yuchen; Hou, Bo; Sorond, Farzaneh A.; Ances, Beau M.; Letendre, Scott; Heaton, Robert K.; et al.
Abstract : Background: Cardiometabolic and cerebrovascular disease are strong independent contributors to cognitive impairment in people living with HIV. Data suggest that cardiovascular risk may play a greater role in cognitive health in women than in men with HIV. Methods: We performed a cross-sectional study of 104 participants with virologically suppressed HIV from 2 clinics in urban China. Participants underwent neuropsychological testing from which we calculated T scores globally and in 5 cognitive domains. We assessed cerebral vasoreactivity of the middle cerebral arteries in response to breath holding. We constructed linear regression models to determine associations between cerebrovascular and cognitive function overall and stratified by sex. Results: Women were younger than men (48 versus 51 years, P = 0.053), had fewer years of education (9 years versus 12 years, P = 0.004), and fewer cardiometabolic risk factors (0 versus 1 factor, P = 0.008). In a model with all participants, cerebrovascular function was significantly associated with global cognition (2.74 higher T score per 1-point higher cerebral vasoreactivity [SE 1.30], P = 0.037). Cerebrovascular function remained significantly associated with global cognition among women (4.15 higher T score [SE 1.78], P = 0.028) but not men (1.70 higher T score [SE 1.74], P = 0.33). The relationships between cerebrovascular function and specific cognitive domains followed a similar pattern, with significant associations present among women but not men. Conclusions: Women with well-controlled HIV may be more vulnerable to the effect of cerebrovascular injury on cognitive health than men. Studies evaluating strategies to protect against cognitive impairment in people living with HIV should include adequate representation of women and stratification of analyses by sex.